BUNGA PEONY DAN BORDIR MOTIF TENUN SEBAGAI SUMBER IDE PENCIPTAAN BUSANA PESTA - Putri, Talisa Fasya Laksita; Indarti, Indarti (Universitas Negeri Surabaya, 2024)
The purpose of this research is to find out the process to the finished result of the application of Peony flower idea source and embroidery weaving motif in the creation of party wear. Peony flowers from Asia and Europe were combined with Western fashion silhouettes and embroidered woven motifs from Indonesia. The research method in this project applies the double diamond model. The process of applying the source idea of Peony flower and embroidered weaving motif to party wear went through several stages. In the first stage, discover, the author took the ITF 2024 & 2025 trend of fusion theme with borderless sub-theme. Define, determine the source of idea of Peony flower and embroidered weaving motif with nude main color through moodboard. In the develop stage, the author did 12 design developments that had been given color and technical drawings digitally. The last stage, deliver, the author realized 1 pair of party wear collection that had received feedback through iteration. The finished result of the application of Peony flower and embroidery motifs in the creation of party wear was right according to the plan, namely women's party wear with bustier cup variations of tulle, mermaid skirt, blooming sleeves, manipulating ruffles gathering gradations and Peony flowers. Men's party fashion in the form of suits, shirts and pants that use embroidered woven motifs on the right side of the suit sleeves and fringe decoration on the front of the suit.